HEGEMONI KASTA DALAM TIGA PROSA KARYA OKA RUSMINI - Putra, I Komang Widana (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2017)
Balinese community?s local tradition frequehtly becomes inspitations to authors in creating their literary works. three prose written by Oka Rusmini in this study  were based on Bali daily life which focuses on caste hegemony nproblems that mostly bexpereinced by the female characters. These three prose are Kenanga novel, Sagra novellette, and Tarian Bumi novel. the results of the analysis showed that caste hegemoni min these three works is reaveled through language, culture, social life, as well as social activities.